The Relationship Between Quality of Nursing Work Life and Work Life Balance of Nurses - S. Dwi Sulisetyawati; Atiek Murharyati; Diyanah Syolihan Rinjani Putri; Anik Sulistyowati (Indonesian Journal of Global Health Research, 2025)
Nurses are health workers who contribute the majority in determining the quality of health services in hospitals. Work life balance is a person's ability to balance the role at work and the role in the family that affects the level of satisfaction of the person. This will have an impact on the nursing services provided. Quality of Nursing work life (QNWL) is an effective way to increase someone's satisfaction in balancing the roles. The purpose of this research is to find out the relationship between QNWL and work life balance of nurses. This research is a quantitative research with a cross sectional approach. The number of respondents was 24 nurses. Sampling using the proportional stratified random sampling technique. The research instrument uses the work life balance and QNWL questionnaires that have been tested for validity and reliability by previous researchers. The correlation between the two variables was tested using the Kendall's Tau test. The characteristics of the respondents are known that most of the nurses are female as many as 16 people (67%), they are in the late adult age that is 36 - 45 years old as many as 9 people (38%), the educational level of Diploma III Nursing as many as 10 people (42%), the length of work >10 years as many as 11 people (46%). Quality of Nursing Work Life (QNWL) of the nurse respondents showed a good category of 21 people (87.5%). Work Life Balance (WLB) of the respondents showed a high category of 24 people (100%). There is no statistically significant relationship between Quality of Nursing Work Life (QNWL) and Work Life Balance (WLB) in this study at the 95% confidence level (p-value = 0.127). Although there is a tendency for a positive relationship, that is, when Work Life Balance increases, the Quality of Nursing Worklife can also increase, but this correlation is weak and not significant.